Understood consent versus informed consent: a new paradigm for obtaining consent for paediatric research studies - Alan F. Isles; Alan F. Isles; Alan F. Isles (Frontiers Media S.A., 2013)
All too often the informed consent process is viewed by members of research teams as a challenge of getting a parent or young person's signature on a form. Informed consent is, however, much more than a signed form. Rather, it is a process, often iterative, in which the parent or young person is given sufficient information about a study in order that they can make a truly informed decision about participation. Substantial effort is required in producing appropriately formatted and readable documents using plain language at about Grade 6 or 12 year old reading level. Achieving truly understood consent involves the researcher spending significant one-on-one time with the parent or young person explaining in simple language what is proposed and then using so-called repeat-back techniques to test the participants understanding. This is critically important if the research involves randomisation to different treatment or use of a placebo arm.